174k views
3 votes
If T(x, y) = (x + 5, y + 6) and Pris the image of P, what is the rule for the translation in which P is the image of P'? T(x, y) = (x – [?], y -[]) Enter the number that belongs in the green box. Enter

User Youxu
by
5.9k points

1 Answer

2 votes

Answer:

The translation is;


T(x,y)=(x-5,y-6)

Step-by-step explanation:

Given the translation rule;


T(x,y)=(x+5,y+6)

when P' is the image of P.

For the inverse, when P is the image of P', the Translation rule would become;


\begin{gathered} x=x^(\prime)+5 \\ x^(\prime)=x-5 \\ y=y^(\prime)+6 \\ y^(\prime)=y-6 \\ So,\text{ the translation rule becomes;} \\ T(x,y)=(x-5,y-6) \end{gathered}

The translation is;


T(x,y)=(x-5,y-6)

User Hammad Haleem
by
4.9k points